The evolution of cognition - Heyes, Cecilia M.; Huber, Ludwig, 1950- (Vienna series in theoretical biology., 2000)
In the last decade, "evolutionary psychology" has come to refer exclusively to research on human mentality and behavior, motivated by a nativist interpretation of how evolution operates. This book encompasses the behavior and mentality of nonhuman as well as human animals and a full range of evolutionary approaches. Rather than a collection by and for the like-minded, it is a debate about how evolutionary processes have shaped cognition. The debate is divided into five sections: Orientations, on the phylogenetic, ecological, and psychological/comparative approaches to the evolution of cognition; Categorization, on how various animals parse their environments, how they represent objects and events and the relations among them; Causality, on whether and in what ways nonhuman animals represent cause and effect relationships; Consciousness, on whether it makes sense to talk about the evolution of consciousness and whether the phenomenon can be investigated empirically in nonhuman animals; and Culture, on the cognitive requirements for nongenetic transmission of information and the evolutionary consequences of such cultural exchange. Contributors : Bernard Balleine, Patrick Bateson, Michael J. Beran, M.E. Bitterman, Robert Boyd, Nicola Clayton, Juan Delius, Anthony Dickinson, Robin Dunbar, D.P. Griffiths, Bernd Heinrich, Cecilia Heyes, William A. Hillix, Ludwig Huber, Nicholas Humphrey, Masako Jitsumori, Louis Lefebvre, Nicholas Mackintosh, Euan M. Macphail, Peter Richerson, Duane M. Rumbaugh, Sara Shettleworth, Martina Siemann, Kim Sterelny, Michael Tomasello, Laura Weiser, Alexandra Wells, Carolyn Wilczynski, David Sloan Wilson